2006
DOI: 10.1136/hrt.2005.082560
|View full text |Cite
|
Sign up to set email alerts
|

Short-term statin treatment improves endothelial function and neurohormonal imbalance in normocholesterolaemic patients with non-ischaemic heart failure

Abstract: Objectives: To investigate the effect of short-term statin treatment on impaired endothelium-dependent vasodilatation and haemodynamic abnormalities typically occurring in chronic heart failure (CHF). Methods: In a double-blind, crossover study endothelium-dependent vasodilatation was measured in conduit and resistance vessels of 23 patients with non-ischaemic CHF after 6 weeks of placebo and 40 mg atorvastatin. The haemodynamic impact was assessed by cardioendocrine hormones, echocardiography and clinical ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 52 publications
0
29
0
1
Order By: Relevance
“…While statins, in general, ameliorate endothelial dysfunction [68][69][70], there is mixed information about their impact on vascular NO responsiveness. For example, in type 1 diabetes mellitus patients, NTG-mediated dilatation in brachial artery increased after 6 weeks of therapy with atorvastatin (40 mg/ day) [69].…”
Section: Statinsmentioning
confidence: 98%
“…While statins, in general, ameliorate endothelial dysfunction [68][69][70], there is mixed information about their impact on vascular NO responsiveness. For example, in type 1 diabetes mellitus patients, NTG-mediated dilatation in brachial artery increased after 6 weeks of therapy with atorvastatin (40 mg/ day) [69].…”
Section: Statinsmentioning
confidence: 98%
“…However, conflicting results on associations between use of hypolipidemic drugs and ED exist. Recent published studies by Taneva et al, 42 Strey et al 43 and Guven et al 44 suggest that statin therapy improves endothelial function, especially among patients with pre-existing endothelium dysfunction 44 and therefore found a potential positive effect from these compounds.…”
Section: Dyslipidemia and Related Drugsmentioning
confidence: 99%
“…Some clinical trials have found that statins lower serum markers of inflammation [3], improve endothelial and cardiac functions [4], and reduced hospitalization rates in patients with CHF [5]. Some large clinical studies have found that statins do not affect clinical outcomes in patients with ischemic heart failure [6] or chronic heart failure of ischemic or nonischemic etiology [7].…”
Section: Introductionmentioning
confidence: 99%